2019
DOI: 10.2147/ceg.s186235
|View full text |Cite
|
Sign up to set email alerts
|

<p>Fecal microbiota profiles in treatment-na&iuml;ve pediatric inflammatory bowel disease &ndash; associations with disease phenotype, treatment, and outcome</p>

Abstract: PurposeImbalance in the microbiota, dysbiosis, has been identified in inflammatory bowel disease (IBD). We explored the fecal microbiota in pediatric patients with treatment-naïve IBD, non-IBD patients with gastrointestinal symptoms and healthy children, its relation to IBD subgroups, and treatment outcomes.Patients and methodsFecal samples were collected from 235 children below 18 years of age. Eighty children had Crohn’s disease (CD), 27 ulcerative colitis (UC), 3 IBD unclassified, 50 were non-IBD symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 50 publications
3
77
3
Order By: Relevance
“…Changes in Prevotella spp. were reported previously, with conflicting results in multiple studies [26,28,31,46]. Our results showed a relatively weak negative association between Prevotella spp.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Changes in Prevotella spp. were reported previously, with conflicting results in multiple studies [26,28,31,46]. Our results showed a relatively weak negative association between Prevotella spp.…”
Section: Discussioncontrasting
confidence: 70%
“…Supporting that hypothesis, most of our results were consistent with published studies with IBD patients. For example, reduced abundance of F. prausnitzii was reported in many studies [22][23][24][25][26][27][28][29]. We found that F. prausnitzii was negatively associated with fecal calprotectin, EPX, and IgA in the current study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Oligofructoseenriched inulin in overweight children has been shown to increase satiety, reduce energy intake as well as BMI and body fat mass over 16 weeks (body weight decrease of 3.1%, percent body fat decrease of 2.4% compared with children given placebo (increase of 0.5%, increase of 0.05% respectively). There is now some evidence that the stool microbiota profiles of patients with inflammatory conditions, such as inflammatory bowel disease, differs from those who are heathy, 166 understand the extent to which clinical success depends on these factors. 167 Indeed, some clinical trials have noted the importance of baseline microbiota composition among responders.…”
Section: [H1] Translation To the Clinicmentioning
confidence: 99%
“…The absence of PXR and CAR also led to an increase in the Lactobacillus genus, corresponding to reduced taurine-conjugated BAs. Lastly, species differences in PXR (mPXR vs. hPXR) also profoundly altered the gut microbiome, including higher Prevotella as well as lower A. muciniphila, both of which are hallmarks of in ammatory bowel disease [73,74], thus caution is warranted when using WT mouse models to study PXR and in ammation, as mPXR carriers may be more resistant to GI in ammation than hPXR carriers.…”
Section: Discussionmentioning
confidence: 99%